Cytotoxicity study of newly-synthesized carbonyl thiourea derivatives on pathogenic Acanthamoeba and its quantitative structure-activity relationship (QSAR) analysis - Ibrahim, Maizatul Akma; Mat Amin, Nakisah; M. Yusof, M. Sukeri; Hasan, M. Noor (2016)
Previous studies proved that certain thiourea derivatives have various biological properties. Therefore, 44 newly-synthesized carbonyl thiourea derivatives which had been successfully synthesized were investigated for their cytotoxicity effects on a pathogenic Acanthamoeba sp. (Hospital Kuala Lumpur isolate), and later proceeded with quantitative structure-activity relationship (QSAR) analysis. Inhibition concentration of 50% the cells population (IC50) after the treatment with the compounds was examined as verification for their cytotoxicity. Two representative compounds from the series were used to evaluate the cells’ membrane integrity after the treatment by acridine orange/propidium iodide (AO/PI) staining. From the IC50 values data obtained, the QSAR analysis of stepwise-multiple linear regression was conducted to generate a model which can correlate the thiourea analogs’ molecular structures with their anti-amoebic activity. Results showed that these thiourea derivatives are positively active against the Acanthamoeba isolate (IC50 = 2.559-7.807 μg/mL). Under the fluorescence microscope, the cells from the AO/PI staining were observed to have lost their membrane integrity. On the other hand, the QSAR analysis for the 44 compounds with the IC50 values were used as the dataset (training; n=30; test; n=14). The pool of descriptors generated by DRAGON software was reduced to a set of relevant numbers by performing pairwise correlation ( > 0.90) and zero or constant variance for greater that 90% of the dataset, giving 202 descriptors. The forward mode of stepwise was later employed to choose the best set of descriptors for the model. After the examination of the correlation matrix and outliers, the final equation model constructed gave a statistically good result with r2 = 0.888, and r2cv = 0.783. The model was validated by prediction on the test set (r2test = 0.789), and y-randomization test. The model gave six variables which were represented by edge adjency indices, Burden Eigenvalue, topological charge indices, and atom-centred fragments. The final model The QSAR model developed in this study might facilitate the search for new compounds with anti-amoebic activity.